Mapping the Future of Occupations: Transformative and Destructive Effects of New Digital Technologies on Jobs - Frank Fossen; Alina Sorgner (Foresight and STI Governance, 2019)
We investigate the impact of new digital technologies upon occupations. We argue that these impacts may be both destructive and transformative. The destructive effects of digitalization substitute human labor, while transformative effects of digitalization complement it. We distinguish between four broad groups of occupations that differ with regard to the impact of digitalization upon them. “Rising star” occupations are characterized by the low destructive and high transformative effects of digitalization. In contrast, “collapsing” occupations face a high risk of destructive effects. “Human terrain” occupations have low risks of both destructive and transformative digitalization, whereas “machine terrain” occupations are affected by both types. We analyze the differences between these four occupational groups in terms of the capabilities, which can be considered bottlenecks to computerization. The results help to identify which capabilities will be in demand and to what degree workers with different abilities can expect their occupations to be transformed in the digital era.